2022
DOI: 10.3389/pore.2022.1610004
|View full text |Cite|
|
Sign up to set email alerts
|

Overall Survival Prediction of Advanced Cancer Patients by Selection of the Most Significant Baseline Serum Biomarker Combination

Abstract: Introduction: Consistent association between elevated baseline serum values and C-reactive protein (CRP), cross-linked fibrin degradation products (D-dimer), lactate dehydrogenase (LDH), decreased baseline serum albumin, absolute lymphocyte count to absolute monocyte count ratio (LMR), elevated absolute neutrophil count to absolute lymphocyte count ratio (NLR), elevated platelet count to absolute lymphocyte count ratio (PLR), and between some combinations of these biomarkers and the short overall survival of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
4
0
5
Order By: Relevance
“…Az alábbiakban a szerző bemutatja néhány metaanalízis és validációs vizsgálat alapján az emelkedett NLR és a rosszindulatú daganatos betegek rövidebb túlélése közötti összefüggést. Továbbá közli saját megfigyeléseit is a munkahelyén kezelt előrehaladott daganatos betegek adatai [9] alapján.…”
Section: Eredeti Közleményunclassified
See 3 more Smart Citations
“…Az alábbiakban a szerző bemutatja néhány metaanalízis és validációs vizsgálat alapján az emelkedett NLR és a rosszindulatú daganatos betegek rövidebb túlélése közötti összefüggést. Továbbá közli saját megfigyeléseit is a munkahelyén kezelt előrehaladott daganatos betegek adatai [9] alapján.…”
Section: Eredeti Közleményunclassified
“…A szerző elemezte a korábbi retrospektív vizsgálata [9] alapját képező ugyanazon betegek adatainak eredményeit az NLR prognosztikai szerepének szempontjából.…”
Section: Az Nlr Prognosztikai Szerepének Vizsgálati Módszere 75 Beteg...unclassified
See 2 more Smart Citations
“…There is growing evidence that a systemic inflammatory response is a major factor of muscle wasting and functional decline in patients with cachexia (4)(5)(6)(7)(8). One of the sensitive measures of the systemic inflammatory response is C-reactive protein (CRP), and various studies have demonstrated the prognostic value of CRP in patients with cancer (9)(10)(11). The Glasgow Prognostic Score (GPS) and modified GPS (mGPS) are the most widely studied inflammation-based prognostic indices incorporating CRP (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%